2021
DOI: 10.3390/plants10091792
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic Pathway of Proanthocyanidins in Major Cash Crops

Abstract: Proanthocyanidins (PAs) are a group of oligomers or polymers composed of monomeric flavanols. They offer many benefits for human fitness, such as antioxidant, anticancer, and anti-inflammatory activities. To date, three types of PA have been observed in nature: procyanidins, propelargonidins, and prodelphinidins. These are synthesized as some of the end-products of the flavonoid pathway by different consecutive enzymatic activities, from the same precursor—naringenin. Although the general biosynthetic pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 105 publications
(166 reference statements)
0
8
1
Order By: Relevance
“…Catechin is a flavonoid that shares the upstream biosynthetic pathway with quercetin [54]. In the flavonoid pathway, dihydroquercetin can diverge into catechin or quercetin by dihydroflavonol (DFR) or flavonol synthase (FLS), respectively [54]. Although an abundant level of catechin was detected in present study, quercetin was barely identified, which is inconsistent with previous report that two flavonoids were both steadily detected in mung bean sprouts [2,55].…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Catechin is a flavonoid that shares the upstream biosynthetic pathway with quercetin [54]. In the flavonoid pathway, dihydroquercetin can diverge into catechin or quercetin by dihydroflavonol (DFR) or flavonol synthase (FLS), respectively [54]. Although an abundant level of catechin was detected in present study, quercetin was barely identified, which is inconsistent with previous report that two flavonoids were both steadily detected in mung bean sprouts [2,55].…”
Section: Discussioncontrasting
confidence: 92%
“…Catechin is a flavonoid that shares the upstream biosynthetic pathway with quercetin [54]. In the flavonoid pathway, dihydroquercetin can diverge into catechin or quercetin by dihydroflavonol (DFR) or flavonol synthase (FLS), respectively [54].…”
Section: Discussionmentioning
confidence: 99%
“…In the flavonoid biosynthetic pathway, proanthocyanidins are the precursors of a branch of the anthocyanidin biosynthetic pathway. Proanthocyanidins and anthocyanins are derived from the same precursor, anthocyanidin, and share a common biosynthetic process for the conversion of phenylalanine to anthocyanidin [92]. Thus, we can conclude that the flavonoid metabolic pathway is more active in the darker infructescences.…”
Section: Phenolicsmentioning
confidence: 78%
“…Similarly, Truzzi et al [32] reported a strong correlation between the expression of quercetin derivatives and cyanidin 3-O-glucoside. The strong positive correlation between anthocyanins and epicatechin (0.4-0.5 **), as well as procyanidin dimer (0.6-0.9 **), reflects that these compounds are direct precursors of anthocyanins synthesis [92]. Furthermore, we were able to determine a strong correlation between anthocyanins and naringenin hexoside 1 (0.5 ** for cyanidin-3-glucoside and cyanidin-3-rutinoside), while the correlation with kaempferol-3-rutinoside was medium (0.3 *).…”
Section: Correlations Between Anthocyanins and Other Metabolites In T...mentioning
confidence: 99%
“…PAs are synthesized via the chorismic acid pathway, phenylpropane metabolic pathway, flavonoid synthesis and proanthocyanidin pathway 9 . The structural genes encoding the enzymes have been identified in the three pathways, including chalcone isomerase ( CHI ), chalcone synthase ( CHS ), leucoanthocyanidin reductase ( LAR ), flavonoid 3′-hydroxylase ( F3′H ), and anthocyanidin reductase ( ANR ) 10 . The “coagulation effect” refers to losing astringency by PA insolubilization by converting soluble PAs into insoluble PAs with acetaldehyde 6 .…”
Section: Introductionmentioning
confidence: 99%